Pengembangan Modul Interaktif Berbasis SDL dalam Menangani Kesulitan Baca Tulis di MI Mambaul Hidayah - Jamilatun Nafi'ah; Dukan Jauhari Faruq (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research focuses on the development of reading and writing modules, as well as the validity and effectiveness of using these modules for children who cannot yet read or write at primary school level. This R&D study developed an interactive module based on Self-Directed Learning (SDL) for pupils in Years 1–6 at MI Mambaul Hidayah. The research was conducted using the ADDIE model, with instruments including observation, interviews, and analysis via a Likert scale. This study produced a key finding: the design of the interactive module, which is structured according to students’ ability levels and features images, illustrations, and QR-code videos as hallmarks of the SDL approach. The results of the validation test by media and material validators indicated that the module is suitable with minor revisions. Based on the results of the pilot test of the interactive reading and writing module, 5 respondents in the small class stated they ‘strongly agreed’ at 96.7%, whilst in the large group pilot test, the percentage of positive student responses was 90.0%, with the breakdown being: Agree: 68.3%, Strongly Agree: 21.7%. This indicates that an interactive reading and writing module based on Self-Directed Learning can assist both students and teachers in addressing reading and writing difficulties at school. This research still has limitations in terms of wider dissemination as its implementation is currently confined to a single institution; it is recommended that further research be conducted through long-term trials, involving the development and refinement of advanced reading and writing modules